Assessment the relationship between health anxiety and iranian nurses’ quality of life: a cross-sectional study - Amoozadeh, Zahra; Ahmadi, Yazdan; Pishgooie, Amir Hosein; Shaidaei, Mehdi Fallah Bagher; Rumyani, Fatemeh; Momen, Reza; Rezaei, Masoud (Frontiers in Psychiatry, 2025)
BackgroundNurses are one of the most important pillars of any health organization, and their mental health is of great importance. Health anxiety is one of the factors that affect the psychological health of nurses and the presence of this disorder among nurses will change their quality of life.ObjectiveThis study was conducted with the aim of investigating the level of health anxiety and its relationship with the quality of life of nurses working in selected hospitals of Aja University of Medical Sciences, Tehran, Iran.MethodologyIn this descriptive-analytical study, 257 nurses working in different departments of selected Aja hospitals were randomly selected and their health anxiety levels were measured using the short version of Salkoskis and Varik’s Health Anxiety Questionnaire and their quality of life was measured using World Health Organization quality of life questionnaire was evaluated. Finally, the relationship between health anxiety and nurses’ quality of life was evaluated.Results257 nurses who met the study entry criteria were randomly selected. Their mean health anxiety was evaluated as 35.21; This statistic shows that nurses’ health anxiety is at an average level. In addition, health anxiety was negatively associated with total score of the QOL (r = - 0.18, P = 0.003). Moreover, this relationship was significant for physical health (r = -0.14, P = 0.01), psychological health (r = -0.30, P <0.001), social relationships (r = -0.31, P <0.001), and social environment(r = -0.21, P <0.001).ConclusionThis study showed that there is a significant relationship between health anxiety and different dimensions of quality of life, so that the quality of life of nurses decreases with the increase of health anxiety.